2018
DOI: 10.1038/s41387-018-0035-z
|View full text |Cite
|
Sign up to set email alerts
|

Maternal betaine supplementation affects fetal growth and lipid metabolism of high-fat fed mice in a temporal-specific manner

Abstract: Background/objectivesMaternal obesity increases the risk of gestational diabetes mellitus (GDM), which results in fetal overgrowth and long-lasting metabolic dysfunctioning in the offspring. Previous studies show that maternal choline supplementation normalizes fetal growth and adiposity of progeny from obese mice. This study examines whether supplementation of betaine, a choline derivative, has positive effects on fetal metabolic outcomes in mouse progeny exposed to maternal obesity and GDM.MethodsC57BL/6J mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 59 publications
1
29
0
Order By: Relevance
“…We have previously shown that the HF-fed mice demonstrate impaired glucose tolerance during pregnancy, resembling the characteristics of GDM [ 23 , 24 , 25 ]. The HF-fed female mice also had higher weight gain and visceral fat weight than the NF-CO mice.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have previously shown that the HF-fed mice demonstrate impaired glucose tolerance during pregnancy, resembling the characteristics of GDM [ 23 , 24 , 25 ]. The HF-fed female mice also had higher weight gain and visceral fat weight than the NF-CO mice.…”
Section: Resultsmentioning
confidence: 99%
“…We confirmed the impaired glucose tolerance of HF mice via intraperitoneal glucose tolerance tests at E11.5 and E15.5. The glucose tolerance test (GTT) results were published in prior studies [ 23 , 24 , 25 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The significant positive association between maternal betaine status and SGA risk, showed in GUSTO, was not found in our study; this can be explained by the limited power of the analysis resulted from the small number of SGA infants. Besides, a recent study showed that maternal betaine supplementation prevented fetal and placental overgrowth in high-fat-fed mice (27) . Maternal plasma betaine have been found to remain constant from twenty-two gestational weeks to the rest of pregnancy (28,29) , a stage covering the period of our blood sample collection.…”
Section: Discussionmentioning
confidence: 99%
“…60 Igf2 is an imprinted gene and maternal choline and betaine decreased the Igf2 expression and fetal adiposity. 61 On the other hand, gestational choline supply increases the histone methylation by simultaneously activating Kmt1c and Kmt1a methyltransferases and increasing the concentration of SAM. 62 Therefore, choline has a long-term epigenomic impacts on human health as presented in numerous benefits of prenatal choline supplementation on neurogenesis, gestational diabetes, and non-alcoholic liver disease.…”
Section: Gene Transcription and Regulation With Choline Availabilitymentioning
confidence: 99%